(NfRANCUZSKO(B-(NRUSSKIJ FRAZEOLOGI^ESKIJ SLOWARX (B:s (NoKOLO (B35 000 (NFRAZEOLOGI^ESKIH EDINIC (B/s - (NgAK(B, (NwLADIMIR gRIGORXEWI^s; (NkUNINA(B, (Ni(B.(Na(B.s; (NlALAEW(B, (Ni(B.(Np(B.s; (NrECKER(B, (Nq(B.(Ni(B.s ((NmOSKWA (B:s (Ngis(B,s, 1963)
(NbIBLIOGR(B.: (NS(B. 17 (56 (NNAZW(B.)s
Keywords: (NfRANCUZSKIJ QZYK (B- (NfRAZEOLOGIQs; (NfRANCUZSKO (B- (NRUSSKIE SLOWARIs